A comparative study of laparoscopic versus open ventral hernia repair - Shyam Kishor Gupta; Albail Singh Yadav; Rajeev Sinha (Asian Journal of Medical Sciences, 2022)
Background: The use of laparoscope in the treatment of abdominal wall hernia repair was first reported in 1993 by LeBlanc and William. But with the passage of time and gaining of expertise, LVHR is now being perform more often but it is still not the gold standard of management. Today the proven advantage laparoscopic ventral hernia repair, open ventral hernia repair is less intraoperative blood loss, shorter hospital stays and early return to normal activity. We tried to compare laparoscopic ventral hernia repair versus open ventral hernia repair in primary ventral hernia. Aims and Objectives: The aim of this study was to compare laparoscopic ventral hernia repair (LVHR) and open ventral hernia repair with respect to the operating time, intraoperative blood loss, intraoperative enterotomy, post-operative complications, hospital stay, and return to normal activity. Retrospective cum prospective study. Materials and Methods: This retrospective cum prospective study was conducted in a tertiary care center teaching hospital, M.L.B. Medical College, Jhansi between January 2020 and June 2021. All consented patients after matching for age, sex, and type of ventral hernia, were allocated to either two groups: Groups A open ventral hernia repair (OVHR) 25 case versus Group B (Laparoscopic ventral hernia) repair 25 case. Results: In our study intraoperative blood loss, post-operative complication, hospital stay, return to normal activity was less in LVHR as compared to OVHR. Operating time was found to be non-significant between two groups and occurrence of inadvertent enterotomy although more in LVHR, was still insignificantly different. Conclusion: The findings of present study demonstrate that LVHR was safe and better when compared with OVHR.